HILANGNYA LITERASI SEJAK USIA DINI - Indah Tunjung Sari; Naela Qatrin Nada; Khoirun Nida Amala; Ana Rahmawati (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2024)
In an increasingly interconnected world, many people, especially children, find it easy to access news and information without critically examining its content. This trend can lead to laziness in reading and understanding, potentially hindering the development of good readers and critical thinkers. The Qur'an, a foundational text in Islamic teaching, emphasizes the importance of reading in the specific section known as Surah Al-Alaq. This research explores the Qur'anic perspective on reading and learning through the interpretative lens of M. Quraish Shihab, a prominent Islamic scholar. The study reveals that literacy extends beyond the mere ability to read and write; it encompasses the capacity to comprehend and critically analyze written content. The research highlights the crucial role of parents in cultivating strong reading habits in children from an early age, enabling them to develop wisdom and intellectual depth. By examining the Qur'anic teachings on reading, this study demonstrates that learning to read critically is fundamental to nurturing an informed and discerning generation. The findings underscore the significance of intentional, thoughtful engagement with text as a means of personal and intellectual growth, drawing inspiration from the Qur'an's first revelation that emphasizes knowledge acquisition.